1998
DOI: 10.1159/000016272
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hypoxia and Glucose Deprivation on Tumour Necrosis Factor-Alpha and Granulocyte- Macrophage Colony-Stimulating Factor Expression in Human Cultured Monocytes

Abstract: Ischaemia in wounds may modulate the expression of tumour necrosis factor-alpha (TNF-α) and granulocyte-macrophage colony-stimulating factor (GM-CSF). The release of these and other cytokines by stimulated macrophages influences wound healing. Our aim was to examine the separate and combined effects of hypoxia and glucose deprivation on TNF-α and GM-CSF mRNA levels in human monocytes isolated from peripheral blood by density gradient centrifugation and purified by adherence. Cells were incubated for a 16-hour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 57 publications
0
22
0
1
Order By: Relevance
“…Inhibition of MCP-1 expression has been reported previously in TNF-␣-stimulated human ovarian carcinoma cell lines cultured under hypoxia/anoxia (48), showing that cells other than M are susceptible to the inhibitory effects of low O 2 tension on MCP-1. Therefore, it is conceivable that expression of MCP-1 is differentially regulated by hypoxia depending on the lineage of the target cell, similarly to what has been reported for other hypoxia-regulated genes (34,49). Interestingly, cell-typespecific modulation of MCP-1 expression has also been observed in response to other stimuli (16).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Inhibition of MCP-1 expression has been reported previously in TNF-␣-stimulated human ovarian carcinoma cell lines cultured under hypoxia/anoxia (48), showing that cells other than M are susceptible to the inhibitory effects of low O 2 tension on MCP-1. Therefore, it is conceivable that expression of MCP-1 is differentially regulated by hypoxia depending on the lineage of the target cell, similarly to what has been reported for other hypoxia-regulated genes (34,49). Interestingly, cell-typespecific modulation of MCP-1 expression has also been observed in response to other stimuli (16).…”
Section: Discussionmentioning
confidence: 58%
“…Genes coding for various inflammatory cytokines, growth, and angiogenic factors were demonstrated to be modulated in M exposed to low O 2 tension both in vitro and in vivo. Specifically, induction of TNF-␣, VEGF, platelet-derived growth factor, fibroblast growth factor ␣␤, IL-6, and IL-1 production by human and/or mouse M (29 -34) and inhibition of GM-CSF expression in LPStreated human M were reported (34). Furthermore, we have shown that hypoxia can act as a costimulus with IFN-␥ or LPS in triggering the transcriptional activation of the inducible isoform of the NO synthase (iNOS) gene in mouse M, eliciting NO production (13,15).…”
mentioning
confidence: 99%
“…Since IL-12 has antiangiogenic properties the up-regulation of tie-2 and the action of angiopoetin adds to the proangiogenic properties of monocytes and macrophages . Other reports demonstrate that monocytes share with primary macrophages and macrophage cell lines the expression of a cluster of hypoxia-inducible genes coding for proinflammatory cytokines/receptors and inflammatory mediators, such as IL-1, TNF and its receptor, IL-6, and arginase-1 (Arg-1) (Lewis et al, 1999;Murdoch et al, 2005;Bosco et al, 2006;Demasi et al, 2003;Koga et al, 1992;Guida and Stewart, 1998;Scannell et al, 1993;Metinko et al, 1992;Lahat et al, 2003;Albina et al, 1995Albina et al, , 2005Louis et al, 1998), and down-regulation of cathepsin C (CTSC) and oligoadenylate synthetase (OASE) (Bosco et al, 2006;Burke et al, 2003;Carta et al, 2001). Thus, some overlap exists in the expression of hypoxia-responsive genes implicated in tissue neo-vascularization and activation among mononuclear phagocytes at various differentiation stages.…”
Section: Hypoxia Modulates Angiogenic and Inflammatory Genes In Monocmentioning
confidence: 99%
“…Hypoxia-induced secretion of proinflammatory cytokines, TNF-a and IL-1, has been found in human alveolar macrophages, blood monocytes and human monocytic cell lines. [73][74][75] Since these proinflammatory cytokines can themselves stimulate VEGF production, 76,77 TNF-a and IL-1 may serve to perpetuate the proangiogenic cytokine milieu in hypoxic areas. Other notable cytokines that appear to be upregulated by hypoxic macrophages include macrophage inhibitory factor (MIF) a cytokine known to be involved in facilitating growth factor-induced tumor and endothelial cell proliferation; 78 and interleukin-18 binding protein, which is known to inactivate the angiostatic factor, interleukin-18.…”
Section: Tam Gene Expression In Response To Tumor Hypoxiamentioning
confidence: 99%